2010
DOI: 10.1186/1476-4598-9-66
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo HRMAS of adult brain tumours: metabolite quantification and assignment of tumour biomarkers

Abstract: BackgroundHigh-resolution magic angle spinning (HRMAS) NMR spectroscopy allows detailed metabolic analysis of whole biopsy samples for investigating tumour biology and tumour classification. Accurate biochemical assignment of small molecule metabolites that are "NMR visible" will improve our interpretation of HRMAS data and the translation of NMR tumour biomarkers to in-vivo studies.Results1D and 2D 1H HRMAS NMR was used to determine that 29 small molecule metabolites, along with 8 macromolecule signals, accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 45 publications
5
55
1
1
Order By: Relevance
“…It is a non-destructive technique that can be applied to tissue prior to immunohistochemical analysis, thus providing a link between metabolite concentrations, pathology, and in vivo magnetic resonance imaging and spectroscopy. To this end, a large body of research tried to identify biomarkers for brain tumor characterization and typing using HRMAS [6, 7, 3033]. The quest for biomarkers usually involves analyzing the behavior of single metabolites or ratios of two metabolites in different groups of patients, but does not exploit the relationship between large numbers of metabolites.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a non-destructive technique that can be applied to tissue prior to immunohistochemical analysis, thus providing a link between metabolite concentrations, pathology, and in vivo magnetic resonance imaging and spectroscopy. To this end, a large body of research tried to identify biomarkers for brain tumor characterization and typing using HRMAS [6, 7, 3033]. The quest for biomarkers usually involves analyzing the behavior of single metabolites or ratios of two metabolites in different groups of patients, but does not exploit the relationship between large numbers of metabolites.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, HRMAS multivariate studies successfully revealed the status of tumor microheterogeneity [9, 13, 15, 17] and detected alterations in tumor metabolism before changes in morphology occurred [12]. These studies combined dimensionality reduction methods such as principal component analysis [14, 20, 22] and metabolite quantification [10, 14–17, 22, 30, 47] with the robust classification methods listed above. Many of the dimensionality reduction methods and classifiers employed combine the data in such a way that the extracted components lack physical meaning.…”
Section: Related Workmentioning
confidence: 99%
“…Increased concentrations of Gly have been detected in brain tumors using in vivo and ex vivo MR spectroscopy (28) and it has been proposed as a marker for grade IV glioma (6). However, in vivo studies have been limited, and the relative frequency of observation, distribution, association with other imaging measures, and potential value as a marker of glioma grade have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…This type of error is well documented for GABA, which poses similar problems (25). Indirect proof regarding the difficulty of D-2HG detection is provided by the fact that despite the high frequency of IDH1 mutations in glioma, high levels of D-2HG, and large number of MRS studies of brain tumors performed over the last 20 years (26)(27)(28), the existence of D-2HG was not reported in the cancer MRS literature until after it was discovered through genomic and ex vivo metabolomic analysis (1,2,13).…”
Section: In Vivo Mrs Of D-2hg In Idh Mutant Tumorsmentioning
confidence: 99%